(untitled) (Jurnal Administro : Jurnal Kajian Kebijakan dan ilmu Administrasi Negara, 2022)
Penelitian< span> ini< span> bertujuan< span> untuk< span> menganalisis< span> deskriptif< span> kerja< span> pegawai< span> di< span> kantor < span>< span>Bappelitbangda< span> Kabupaten< span> Minahasa < span> Penelitian< span> ini< span> menggunakan< span> metode< span>< span> deskriptif< span> yang< span> dipadukan< span> dengan< span> pendekatan< span> kualitatif < span> Hasil< span> yang< span> ditemukan< span>< span>< span>adalah;< span> 1 < span> Target< span> kerja< span> di< span> Bappelitbangda< span> Kabupaten< span> Minahasa< span> khususnya< span>< span>< span>dibidang< span> lapangan< span> dapat< span> dikatakan< span> tercapai< span> karena< span> adanya< span> monitoring< span> dan< span>< span>< span>evaluasi < span> namun< span> kendala< span> yang< span> sering< span> dihadapi< span> dalam< span> pencapaian< span> target< span> kerja< span> dari< span>< span>< span>masing< span> < span>masing< span> bidang< span> adalah< span> kurangnya< span> kedisiplinan< span> pegawai< span> dalam< span>< span>< span>melaksanakan< span> kewajiban< span> dalam< span> hal< span> ini< span> waktu< span> kerja < span> pembuatan< span> laporan< span> harian < span>< span>< span>dokumen< span> penting< span> dan< span> laporan< span> koordinasi< span> yang< span> sering< span> terlambat < span> serta target< span>< span>< span>anggaran< span> yang< span> sering< span> tidak< span> tercapai< span> karena< span> adanya< span> refocusing;< span> 2 < span> Pegawai< span>< span>< span>Bappelitbangda< span> Kabupaten< span> Minahasa< span> yang tidak disiplin< span> dalam< span> menjalankan< span>< span>< span>kewajibannya< span> dalam< span> hal< span> masuk< span> kerja< span> dan< span> ketentuan< span> jam< span> kerja< span> berangkat< span> kerja< span>< span>< span>pukul< span> 08 00< span> WITA< span> dan< span> pulang< span> kerja< span> 17 00< span> WITA < span> masih< span> banyak< span> pegawai< span> yang< span>< span>< span>datang< span> terlambat < span> Izin< span> pada< span> jam< span> kerja< span> untuk< span> melakukan< span> aktivitas< span> pribadi < span> dan< span>< span>< span>pimpinan< span> tidak< span> tegas< span> karena< span> selalu< span> memberikan< span> izin< span> kepada< span> pegawai< span> itu< span> sendiri< span>< span>< span>berkurang< span> dan< span> berdampak< span> pada< span> instansi< span> yang< span> ada< span>< span>< p>